Public perception and awareness towards Shah Alam Low Carbon City Program. - Nasrudin, Na’asah; Abdul Rauf, Anis Shahira; Yaman, Rostam; Ismail, Farrah Zuhaira; Ahmad, Noraini (2020)
Climate change and global warming is the real phenomenon that is affecting the well-being of human and living things on earth. The main contributor to this problem is from the greenhouse gases (GHG) emission that consist of carbon dioxide (CO2) from the uncontrolled development which is from urbanisation, economic growth and population growth. Under the Low Carbon City Framework, there are four elements highlighted but, in this research, only one element will be studied which is Transportation Element. The reason why transportation element was chosen is because it is closer to the society and the related information regarding the element are easy to obtain. Aspect such as Private Transport or Single Occupancy Vehicles, Public Transport, Low Carbon Transport, Walking and Cycling, Traffic management were assessed through public approach in order to understand the situation better. Therefore, public involvement is a must to help reducing the global warming effect. Shah Alam is known for its approach to achieve Low Carbon City by 2030. Numerous program and facilities were held and provided to show that authorities are taking serious action about this matter, thus prove that they played an important role. Therefore, Shah Alam under the jurisdiction of MBSA were chosen as case study for the implementation of Low Carbon City Program.